Respuesta :
To solve for (fog)-4)
Replace x in the g(x) equation with -4 and solve, then replace x in f(x) with the solution and solve for final answer.
G(x) = -4(-4) -12 = 16 -12 = 4
F(x) = 3(4)^2 -5(4) -4 = 48 -20 -4 = 24
The answer is 24
✏️ FUNCTIONS
[tex]\purple{\underline {\bold{\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: }}}[/tex]
[tex] \bold \purple{PROBLEM:}[/tex]
» Given the definitions of f(x) and g(a) below, find the value of (f • g)(-4).
- f(x) = 3x2 – 5x – 4
- g(x) = -4x – 12
[tex]\bold \purple{FORMULA:}[/tex]
[tex] \underline{ \boxed{ \rm{ \green{(f \: • \: g)( - 4) }}}}[/tex]
[tex]\bold \purple{SOLUTION:}[/tex]
Substitute the value of x into the given value which is -4. Lets simplify it.
[tex]» \: \rm{(f \: • \: g)(-4) = [3 {x}^{2} – 5x – 4] \: • \: [-4x – 12]}[/tex]
[tex]» \: \rm{(f \: • \: g)( \green{-4}) = [3 {( \green{ - 4})}^{2} – 5( \green{ - 4}) – 4 ]\: • \: [-4( \green{- 4})– 12]}[/tex]
[tex]» \: \rm{(f \: • \: g)( \green{-4}) =[ 3( \green {16}) – ( \green{ - 20}) – 4 ]\: • \:[ ( \green{16})– 12]}[/tex]
[tex]» \: \rm{(f \: • \: g)( \green{-4}) = [ \green {48}– ( \green{ - 20}) – 4 ]\: • \:[ ( \green{4})]}[/tex]
[tex]» \: \rm{(f \: • \: g)( \green{-4}) =[ \green{ 64}] \: • \: [( \green{4})]}[/tex]
[tex]» \: \rm{(f \: • \: g)( \green{-4}) = \underline{\boxed{\green{256}}}}[/tex]
[tex]\bold \purple{ANSWER:}[/tex]
[tex]» \: \rm{(f \: • \: g)( \green{-4}) = \underline{\boxed{\green{256}}}}[/tex]
- Hence, the answer is 256.
[tex]\purple{\underline {\bold{\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: }}}[/tex]
\(^.^\)